2007
DOI: 10.1088/0953-8984/19/26/266217
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pressure on the magnetic properties of TM3[Cr(CN)6]2·12H2O

Abstract: Effect of pressure on magnetic properties of magnetic nanoparticles, based on Prussian blue analogues, were studied in pressures up to 1.2 GPa. The Mn 3 [Cr(CN) 6 ] 2 · nH 2 O and Ni 3 [Cr(CN) 6 ] 2 · nH 2 O nanoparticles were prepared by reverse micelle technique. Transmission electron microscopy images show nanoparticles with average diameter of about 3.5 nm embedded in an organic matrix. The characteristic X-ray peaks of nanoparticles are more diffused and broader. Systems of nanoparticles behave as systems… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
70
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(76 citation statements)
references
References 15 publications
5
70
1
Order By: Relevance
“…The increase in Curie temperature under pressure was ascribed to the enhancement of antiferromagnetic interaction as the consequence of the exchange pathway shortening. In our earlier work we have shown that for PBA with domination of antiferromagnetic interaction the Curie temperature increases under pressure while for those with dominating ferromagnetic it remains unchanged or slowly decreases [7]. The applied pressure can slightly affect bonding angles between magnetic ions mediated by the cyano-bridge.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…The increase in Curie temperature under pressure was ascribed to the enhancement of antiferromagnetic interaction as the consequence of the exchange pathway shortening. In our earlier work we have shown that for PBA with domination of antiferromagnetic interaction the Curie temperature increases under pressure while for those with dominating ferromagnetic it remains unchanged or slowly decreases [7]. The applied pressure can slightly affect bonding angles between magnetic ions mediated by the cyano-bridge.…”
Section: Introductionmentioning
confidence: 95%
“…The applied pressure can slightly affect bonding angles between magnetic ions mediated by the cyano-bridge. A small deviation from the ideal value 180• of the bonding angle can even reduce the strength of magnetic coupling, and results in reduction of T C [7]. Unusually high value of magnetic Grűneisen parameter ε (in the range 9.03-9.97) was reported for PBA [8].…”
Section: Introductionmentioning
confidence: 97%
“…These transitions can be as simple as low ↔ high spin in an isolated molecule or as complex as antiferromagnetic ↔ ferromagnetic, metamagnetic, and quantum critical processes in extended solids [2][3][4][5][6][7][8][9][10][11][12] . Spin crossovers in 4 and 5d-containing compounds are particularly interesting because spin-orbit coupling competes with electron correlations to reveal exotic properties [13][14][15][16][17][18][19] .…”
Section: Introductionmentioning
confidence: 99%
“…In order to distinguish between these magnetic crossover mechanisms, we ventured beyond high mag- 6 ] under pressure. Combining our findings with displacement patterns and anticipated mode trends for (i) an isolated on-site high → low spin transition, (ii) a spin-lattice assisted crossover, and (iii) electron transfer (or charge ordering) induced spin transition reveals that while the spin transition takes place on the Ru dimer, it is enabled by cooperative local lattice distortions around the Cr center.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation